Differential particle size analysis of jabuticaba bark flour (Myrciaria cauliflora Berg) (Research, Society and Development, 2020)
The present article aims to produce and evaluate the differential particle size profile of jabuticaba bark flour. The flour of the jabuticaba bark was obtained through the convective drying process, performed in an air circulation oven at a temperature of 50 °C and a speed of 1.0 m/s for 24 h. The particle size analysis was performed by sieving 50 g of jabuticaba bark flour, using a series of standardized sieves in the range of 9 to 200 mesh. The mathematical models adjusted to the experimental data were Gates-Gaudin-Schuhmann (GGS) and Rosin-Rammler-Bennet Model (RRB). From the experimental data obtained it was verified that the flour of the jabuticaba bark analyzed is in accordance with the criteria of the legislation for granulometric classification. Among the applied mathematical models, the Rosin-Rammler-Bennet (RRB) model was the best fit to the experimental data with coefficient of determination (R2) greater than 0.99, and also presenting the highest inclination angle of the line. It is noteworthy that the average diameter of the particles obtained for fine flour did not differ from the value found experimentally. And that 27.62% for a total of 50 grams of flour had a fine grain size, less than 60 mesh, which is expected and satisfactory for flour characteristics, presenting potential for use in the development of new food products.